A survey of empirical performance evaluation of permissioned blockchain platforms: Challenges and opportunities. Issue 100 (January 2021) - Dabbagh, Mohammad; Choo, Kim-Kwang Raymond; Beheshti, Amin; Tahir, Mohammad; Safa, Nader Sohrabi
Abstract: Blockchain-based platforms, particularly those based on permissioned blockchain, are increasingly popular in a broad range of settings. In addition to security and privacy concerns, organizations seeking to implement such platforms also need to consider performance, especially in latency- or delay-sensitive applications. Performance is generally less studied in comparison to security and privacy, and therefore in this paper we survey existing empirical performance evaluations of different permissioned blockchain platforms published between 2015 and 2019, using a comparative framework. The framework comprises ten criteria. We then conclude the paper with a number of potential future research directions.